1997
DOI: 10.1038/386510a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of natural killer cells by a cytomegalovirus MHC class I homologue in vivo

Abstract: Herpesviruses, such as murine and human cytomegalovirus (MCMV and HCMV), can establish a persistent infection within the host and have diverse mechanisms as protection from host immune defences. Several herpesvirus genes that are homologous to host immune modulators have been identified, and are implicated in viral evasion of the host immune response. The discovery of a viral major histocompatibility complex (MHC) class I homologue, encoded by HCMV, led to speculation that it might function as an immune modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
166
6
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(177 citation statements)
references
References 29 publications
4
166
6
1
Order By: Relevance
“…For HCMV, several mechanisms to escape cellular immune attack have recently been described (Wiertz et al, 1996 a, b ;Hengel et al, 1996 ;Farrell et al, 1997). However, mechanisms of HCMV to escape humoral immune response, as shown for human immunodeficiency virus, have not been described (Schreiber et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For HCMV, several mechanisms to escape cellular immune attack have recently been described (Wiertz et al, 1996 a, b ;Hengel et al, 1996 ;Farrell et al, 1997). However, mechanisms of HCMV to escape humoral immune response, as shown for human immunodeficiency virus, have not been described (Schreiber et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…MCMV has one-upped the ante in this battle by encoding m144, an MHC class I homologue, that both avoids recognition by the adaptive immune system and tricks NK cells into thinking that the cell has 'normal' expression of MHC. Indeed loss of m144 results in reduced virulence, 140 probably as a result of NKmediated killing. (c) We now know that MCMV-resistance in Cmv1 r strains is mediated by the presence of the Ly49H stimulatory receptor on NK cells.…”
Section: Model For the Role Of Ly49h In MCMV Resistancementioning
confidence: 99%
“…142 Recent evidence indicated that MCMV deploys an MHC class I homologue that serves to evade the host immune response. 140 Expression of this virally-encoded MHC class I homologue (m144) would serve the virus in two ways; first by interrupting the surveillance and destruction of the infected cell by virus-specific CD8 cytotoxic lymphocytes and second by engaging the MHC the class I specific inhibitory receptors of NK cells to avoid NK killing (Figure 4b). This is supported by in vivo experiments showing that deletion of the m144 gene results in reduced viral titers in Cmv1 s MCMV-susceptible mice, suggesting that this MCH class I homologue interferes with NK cell cytotoxic activity, likely via an inhibitory NK receptor.…”
Section: Model For the Role Of Ly49h In MCMV Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has indicated that the binding of killer cell inhibitory receptor (KIR) on CD8+cells with E antigen of HLAclass I molecules on virus-infected cells can inhibit the cytolytic activity of CD8+cells against infected cells (69). Cytomegalovirus (CMV)infection is reported to occasionally promote the exacerbation of SLE (70), and a glycoprotein homologous with HLAclass I antigens is encoded by CMVand is known to be a ligand of KIR (71). This mechanism may be related to the inhibition of the killing of CMVby CTL and/or NK cells.…”
Section: ) (58)mentioning
confidence: 99%